# Integrate the functions. Let x + 2 = x + 2 = A(4 -2x) + B

Now, equating the coefficients of x and constant term on both sides, we get,

-2A = 1

A = 4A + B = 2

B = 4

x + 2 = Now,  Now, let us consider, Let 4x – x2 = t

(4 -2x) dx= dt …(1)

And, Now let us consider, Then, 4x – x2 = -(-4x + x2)

= (-4x + x2 + 4 – 4)

= 4 – (x - 2)2

= (2)2 – (x - 2)2 …(2)

using eq. (1) and (2), we get, Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Fundamental Integration Formula59 mins  Interactive Quiz on Integration by Substitution47 mins  Lecture on Integration by parts55 mins  Lecture on some forms of integration54 mins  Lecture on integration by partial fractions62 mins  Interactive Quiz on Integration by Parts56 mins  Integration by Substitution56 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 